2021
DOI: 10.3928/1081597x-20210506-01
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of IOL Power Calculation Formulas for a Trifocal IOL in Eyes With High Myopia

Abstract: PURPOSE: To analyze the results of new intraocular lens (IOL) formulas (Emmetropia Verifying Optical [EVO], Kane, Olsen, and Barrett Universal II), traditional formulas (Haigis and SRK/T), and modified Wang-Koch axial length adjustment formulas with the SRK/T and Holladay 1 (SRK/T modified-W/K and H1 modified-W/K ) in Chinese patients with long eyes. METHODS: In this ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This study was able to add that the Kane, EVO, and SRK/T-CMAL formulas performed similarly to BU-II and Hill-RBF in predominately Caucasian eyes. Similar studies in four Asian populations and one European population also found newer-generation formulas such as the Kane, EVO, and BU-II to be most accurate in long eyes [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 61%
“…This study was able to add that the Kane, EVO, and SRK/T-CMAL formulas performed similarly to BU-II and Hill-RBF in predominately Caucasian eyes. Similar studies in four Asian populations and one European population also found newer-generation formulas such as the Kane, EVO, and BU-II to be most accurate in long eyes [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 61%
“…This is particularly relevant for intraocular lens (IOL) power calculations, where accurate biometric data are essential for optimal visual outcomes [20,21]. The study's findings could inform the development of more precise biometric models for IOL power calculations, especially in patients with extreme ALs [22]. The correlation between the PSL and the AL, especially in cases of high myopia, underscores the role of posterior segment elongation in the progression of myopia.…”
Section: Discussionmentioning
confidence: 88%
“…A similar trend was also noted in high myopes with trifocal IOL calculations. The Barrett Universal II, Olsen, Kane, and EVO 2.0 formulas produced a statistically lower median absolute error than the SRK/T formulas (p < 0.05) [ 8 ]. Moreover, the Barrett Universal II formula produced higher percentages of eyes within ±0.50 D of the prediction error compared to the SRK/T formula (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Barrett Universal II formula produced higher percentages of eyes within ±0.50 D of the prediction error compared to the SRK/T formula (p < 0.05). However, there were no significant differences in the prediction accuracy of all formulas tested in axial lengths less than 28 mm [ 8 ].…”
Section: Discussionmentioning
confidence: 99%